2021
DOI: 10.1039/d1py01039e
|View full text |Cite
|
Sign up to set email alerts
|

Cocatalyst versus precatalyst impact on the vinyl-addition polymerization of norbornenes with polar groups: looking at the other side of the coin

Abstract: Polymers derived from norbornenes with polar groups are of interest as modular templates and materials for membrane processes and microelectronic applications due to the attractive combination of their properties. However,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Recently, it has been demonstrated that (NHC)Pd-based systems cat-alyze vinyl-addition polymerization of various functionalized norbornenes [14][15][16][17][18][19][20][21]. For instance, these systems showed good catalytic activity in polymerization of norbornenes with hydroxy [20,22], ether [21], ester [14,15,[18][19][20]23,24], imide [14,16,17], silyl [14,19,20,24], and alkyl/alkenyl [19,20,22,24,25] functionality. At the same time, to the best of our knowledge, the polymerization of norbornene-type monomers with reactive halogen-containing groups over (NHC)Pd-catalysts has not yet been reported.…”
Section: Vinyl-addition Polymerization Of 5-bromoalkylnorbornenesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, it has been demonstrated that (NHC)Pd-based systems cat-alyze vinyl-addition polymerization of various functionalized norbornenes [14][15][16][17][18][19][20][21]. For instance, these systems showed good catalytic activity in polymerization of norbornenes with hydroxy [20,22], ether [21], ester [14,15,[18][19][20]23,24], imide [14,16,17], silyl [14,19,20,24], and alkyl/alkenyl [19,20,22,24,25] functionality. At the same time, to the best of our knowledge, the polymerization of norbornene-type monomers with reactive halogen-containing groups over (NHC)Pd-catalysts has not yet been reported.…”
Section: Vinyl-addition Polymerization Of 5-bromoalkylnorbornenesmentioning
confidence: 99%
“…The molecular weights of such polymers were usually insufficient to cast freestanding and robust polymer films. Recently, it has been demonstrated that (NHC)Pdbased systems catalyze vinyl-addition polymerization of various functionalized norbornenes [14][15][16][17][18][19][20][21]. For instance, these systems showed good catalytic activity in polymerization of norbornenes with hydroxy [20,22], ether [21], ester [14,15,[18][19][20]23,24], imide [14,16,17], silyl [14,19,20,24], and alkyl/alkenyl [19,20,22,24,25] Intriguing results were obtained when studying the polymerization of M1-M4 on these (NHC)Pd-catalysts.…”
Section: Vinyl-addition Polymerization Of 5-bromoalkylnorbornenesmentioning
confidence: 99%
“…The influence of the cocatalyst was largely determined by the nature of the utilized monomer. The obtained polymers exhibited satisfactory film‐forming properties 6 . In addition, diverse functionalized polynorbornenes, which are not realizable via the conventional post‐polymerization functionalization or the direct polymerization strategies, were also synthesized through the vinyl‐addition copolymerization of norbornene and alkenyl‐norbornenes by employing α‐substituted benzylic complexes of palladium (II) catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained polymers exhibited satisfactory film-forming properties. 6 In addition, diverse functionalized polynorbornenes, which are not realizable via the conventional post-polymerization functionalization or the direct polymerization strategies, were also synthesized through the vinyl-addition copolymerization of norbornene and alkenyl-norbornenes by employing α-substituted benzylic complexes of palladium (II) catalysts. The incorporation of desired functional groups into the polymer skeleton was further accomplished through hydrosilylation or hydroboration reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have shown that two-and three-component systems based on N-heterocyclic carbene Pd-complexes ((NHC)Pd-complexes) with allyl ligands exhibited high catalytic activity, good tolerance to functional groups, and catalyzed VAP of various norbornenes in air. 55,56 Based on these results and taking into account the literature data indicating that cationic Pd-complexes with a Pd−C bond, a labile ligand, and a weak coordinating anion can serve as onecomponent VAP catalysts, we have developed a set of cationic (NHC)Pd(allyl)-complexes as new one-component VAP catalysts. The synthesized complexes had a good stability in air in solutions and in the solid state, which made it possible to carry out polymerization in air.…”
Section: ■ Introductionmentioning
confidence: 99%